Estimation of Parameters and Verification of Statistical Hypotheses for Gaussian Models of Stock Price - Marushkevych, Dmytro; Munchak, Yevheniia (Lithuanian Journal of Statistics, 2016)
We construct models of asset prices on the Ukrainian stock market and analyse their applicability by checkingappropriate statistical hypotheses using actual observed data. We also analyse the presence of jumps in the dynamics ofdifferent assets and estimate the Hurst coefficient for the logarithm of the price of the asset by two different methods.
Keywords: Ukrainian stock market; Ukrainian Stock Exchange; fractional Brownian motion; estimation of Hurst coefficient